Turning our students into teachers for the day, to enhance learning and help the community - Andrew N. Williams; Wan Mohamad Wan Abdullah (2013)
Real-life tasks, where our students have to use language for a real purpose, are excellent ways to develop deeper language skills and are highly motivating. This paper reports on a project in which students learning English were asked to teach English to children in the community around them using fun activities. It was hoped that through the processes of preparing material to teach and the teaching itself, these students would acquire deeper understanding and improved confidence and fluency. This activity has been carried out on three occasions with undergraduate students on an English proficiency course running English activities for primary school children. The undergraduates involved, whose English proficiency ranged from beginner levels to upper-intermediate levels, considered this activity beneficial to the extent of requesting to repeat the activity again. This paper will describe how this activity was carried out, problems encountered, observed results and feedback obtained from the students and communities involved.